2020
DOI: 10.2144/fsoa-2019-0120
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Versus Stereotactic Radiotherapy for Treatment of Pulmonary metastases. a Systematic Review of Literature

Abstract: It is not clear as to which is the best treatment among surgery and stereotactic radiotherapy (SBRT) for lung oligometastases. A systematic review of literature with a priori selection criteria was conducted on articles on the treatment of pulmonary metastases with surgery or SBRT. Only original articles with a population of patients of more than 50 were selected. After final selection, 61 articles on surgical treatment and 18 on SBRT were included. No difference was encountered in short-term survival between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 94 publications
0
29
1
Order By: Relevance
“…1,2 While pulmonary metastasectomy is the standard treatment for patients with a limited metastatic pattern, several retrospective studies have shown that x-ray stereotactic body radiation therapy (SBRT) yields short-term promising outcomes that are comparable to those of surgery. 3,4 Proton beam therapy (PBT) can reduce the volume of and radiation dose to the surrounding normal tissues using the sharp Bragg peak fall-off, as demonstrated in previous dosimetry studies. 5,6 Based on increasing evidence for the use of PBT for early-stage lung tumors, which show acceptable outcomes with the potential benefit of reducing toxicities, PBT seems to yield outcomes similar to those of x-ray SBRT for pulmonary oligometastases.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,2 While pulmonary metastasectomy is the standard treatment for patients with a limited metastatic pattern, several retrospective studies have shown that x-ray stereotactic body radiation therapy (SBRT) yields short-term promising outcomes that are comparable to those of surgery. 3,4 Proton beam therapy (PBT) can reduce the volume of and radiation dose to the surrounding normal tissues using the sharp Bragg peak fall-off, as demonstrated in previous dosimetry studies. 5,6 Based on increasing evidence for the use of PBT for early-stage lung tumors, which show acceptable outcomes with the potential benefit of reducing toxicities, PBT seems to yield outcomes similar to those of x-ray SBRT for pulmonary oligometastases.…”
Section: Introductionmentioning
confidence: 98%
“… 1 , 2 Although pulmonary metastasectomy is the standard treatment for patients with a limited metastatic pattern, several retrospective studies have shown that x-ray stereotactic body radiation therapy (SBRT) yields short-term promising outcomes that are comparable to those of surgery. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Local control rates were excellent at 100% and 96% at 1-and 2-year follow-up respectively (20). Similar high local control rates in the order of magnitude of 90% at 1 year and 80% at 2 years have been reported in retrospective studies, again including a multitude of primary tumors (39,(62)(63)(64). De Rose et al reported on 60 NSCLC patients with 90 lung metastases treated with SBRT (64).…”
Section: Outcome Per Location: An Intricate Interplay Of Dose Volume and Primary Tumormentioning
confidence: 61%
“…This difference in outcome seems to especially hold for lesions larger than 2 cm (72). In retrospective studies, surgery tends to either have similar or better outcomes than radiotherapy (62,66,73). Yet, when comparing different treatment modalities using retrospective data, the results are inherently biased.…”
Section: Outcome Per Location: An Intricate Interplay Of Dose Volume and Primary Tumormentioning
confidence: 99%
“…Therefore, a detailed histological clarification should be pursued to plan further therapeutic measures and to predict survival. Recently, LONDERO et al [52] reviewed and compared the outcome following SBRT and surgery for the treatment of pulmonary metastases. 61 articles on surgery and 18 on SBRT were found to be eligible, each with cohorts of >50 patients.…”
Section: Lung Oligometastasesmentioning
confidence: 99%